2008
DOI: 10.1080/00397910802369646
|View full text |Cite
|
Sign up to set email alerts
|

Praseodymium-Induced Pinacol Formation

Abstract: In an attempt to regenerate Ti(0) from TiO x for possible application in a catalytic McMurry coupling reaction, a praseodymium-based pinacol reaction was uncovered. This reaction formed the two products 2,3-diphenyl-2,3-butanediol (3) and a,b-dimethyl-a-phenyl-b-[(trimethylsilyl)oxy]-benzene-ethanol (6) in a 1:3 ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Imamoto et al discovered that a simple praseodymium chloride salt combined with lithium reagents could efficiently yield alcohols from carbonyl compounds under mild conditions . Priefer et al reported that the in situ formed reagents of Pr 0 /TMSCl induced carbon–carbon coupling of ketones to generate pinacols . Zhang et al studied the Barbier-type reaction with praseodymium reagents, which showed efficient insertion of the carbon–iodide bond of allyl iodide to yield the organometallic complex, reacting with ketones under mild conditions without any additives .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Imamoto et al discovered that a simple praseodymium chloride salt combined with lithium reagents could efficiently yield alcohols from carbonyl compounds under mild conditions . Priefer et al reported that the in situ formed reagents of Pr 0 /TMSCl induced carbon–carbon coupling of ketones to generate pinacols . Zhang et al studied the Barbier-type reaction with praseodymium reagents, which showed efficient insertion of the carbon–iodide bond of allyl iodide to yield the organometallic complex, reacting with ketones under mild conditions without any additives .…”
mentioning
confidence: 99%
“…8 Priefer et al reported that the in situ formed reagents of Pr 0 /TMSCl induced carbon− carbon coupling of ketones to generate pinacols. 9 Zhang et al studied the Barbier-type reaction with praseodymium reagents, which showed efficient insertion of the carbon−iodide bond of allyl iodide to yield the organometallic complex, reacting with ketones under mild conditions without any additives. 10 In 2017, Pan et al discovered that Pr(OTf) 3 -catalyzed regioselective amination using azides could produce C3−Nsubstituted coumarins.…”
mentioning
confidence: 99%
“…However, the use of zerovalent lanthaniod metals in Barbier reaction was still limited to Sm . To the best of our knowledge, only a few cases using praseodymium metal directly in organic synthesis have been reported . Very recently, our group became deeply interested in the application of lanthanide metals in organic synthesis .…”
mentioning
confidence: 99%